Chronic corporate performance in media-tech firms: a new perspective. Issue 4 (2nd October 2022) - Oliver, John J.
ABSTRACT: This paper investigates how a crisis event resulted in the long-term decline in media-tech firm performance. The research developed an intellectual bridge and transfer of knowledge between the previously discrete fields of Strategic Management and Epigenetics. The study used a multi-method approach consisting of the critical incident technique, longitudinal content analysis of corporate annual reports and financial analysis which divided the data into "what happened before the crisis event" and "what happen after the crisis event". The paper concludes that by examining failed corporate turnaround and chronic performance through the lens of epigenetics, we are better able to understand how a crisis event can create transgenerational responses which result in adaptive cultural norms that combine to consolidate corporate underperformance.